Disposal of the equipment for measurement of the air temperature in buildings - Barbosa, Miriam Jerônimo (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper analyses the influence of the position of the indoor air temperature sensors. The concern about the position of sensors has been pointed out by post-occupancy studies, in which the users must cohabit with the equipment without affecting the results. Measurements of air temperature in a building constructed in wood and another in masonry were performed, placing the sensor in the centre of the environment and next to sun-exposed surfaces. For each position in the room, sensors were placed in three heights; and, for each height, protected and not protected from thermal radiation, resulting in 18 points of measurement in each building. The results have been analyzed to verify the conformity of these with the specifications of technical standards that establish places and heights for these measurements: PNBR 02:136.01 - 001, ASHRAE 55 and ISO 7726. The results are in agreement with those standards, which indicate the centre of the room and height of 1.10m as being representative of the whole environment. The results also showed a greater influence of the measurement place in the building with masonry walls.